Tinjauan Atas Prosedur Penjualan Rumah Secara Kredit Pada Perumahan Royal Tajur Residence - Hanipah, R Siti; Listari, Sinta; Pardede, Robert Pius (Program Vokasi dan LPPM IBI Kesatuan, 2024)
The procedure for selling a house on credit is a house selling process where the buyer can pay in stages over an agreed period of time. Fulfilling housing needs is an individual right that is entirely the responsibility of each individual. In this context, developers position themselves as facilitators in meeting housing needs. The development of property and banking has recently been quite rapid, making it easier for individuals to own a house on credit. The purpose of this writing is to find out that the procedures for selling houses on credit carried out at the Royal Tajur Residence housing complex are in accordance with applicable regulations and can be accounted for as well as identifying obstacles and obstacles that may be faced in the process of selling houses on credit. The results of this writing show that The procedure for selling houses on credit at the Royal Tajur Residence housing complex is in accordance with applicable regulations. The evaluation results in this writing show that the procedure for selling houses on credit at the Royal Tajur Residence housing complex has been successful in achieving the objectives of the writing. However, there are several aspects that need to be improved by developers, such as providing clear and transparent information regarding credit requirements that must be met by consumers before making a purchase, evaluating potential consumers and avoiding giving credit to consumers who have a history of bad credit or financial problems as well as providing useful information. clear and transparent regarding the time of delivery of credit objects. Keywords: developer, property, credit sales.